Edukasi Gizi dan Pengolahan Pangan Berbahan Kelor Sebagai Upaya Preventif Stunting di Desa Wates - Ashivatuszahra, Aviara Jeka; Hurin'in, Nazilah; Firdaus, Salsabila; Ardiansyah, Mohammad Yayan; Ulla, Umul Fadilatul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Stunting is a chronic nutritional problem that hinders child growth and is still a serious challenge in Indonesia, including in Wates Village area, Pasuruan District. The high rate of stunting in the village is due to the lack of knowledge of the community regarding nutrition as well as not yet optimal utilization of local nutritious foodstuffs. To address this issue, KKN Team 17 from UIN Sunan Ampel Surabaya initiated a nutrition education and food processing training program based on currant leaves (Moringa oleifera), which is known to have a high nutrient content. The program was run through the MP-ASI School activity entitled “Provisions Prevent Stunting Early” that targeted mothers with toddlers, through material delivery, kelor pudding cooking demonstration, interactive discussions, as well as comprehension evaluation. The implementation results showed there was an increase in participants’ understanding regarding the importance of balanced nutrition and the benefits of kerosene leaves as a local food source, as well as the emergence of willingness to start consuming and processing kerosene in the daily menu. This activity affirms that a community-based educational approach and the utilization of local potential can be an effective strategy in preventing stunting sustainably.